Utility sector of tourism infrastructure in Industry 4.0: challenges and solutions - N. Chernenko; A. Kukharuk; Ya. Hlushchenko; O. Korohodova (Вісник Харківського національного університету імені В.Н. Каразіна: Серія Економіка)
This article is an original attempt to define the necessity of providing the components of Industry 4.0 of the utility sector of tourism infrastructure. The problem is that the tourism utility sector faces challenges in Industry 4.0, such as the need for infrastructure modernization, digital integration, sustainability, and meeting changing tourist expectations. The study is conducted based on data from four (Croatia, Albania, Portugal, Montenegro) leading countries in terms of international tourism receipts as a percentage of GDP, as well as Romania and Ukraine as countries with great tourism potential. The significant impact of Industry 4.0 technologies on the development of tourism in these countries, is proved in this article. This study seeks to investigate the obstacles encountered by the tourism infrastructure utility sector in Industry 4.0 and suggests solutions to overcome these challenges. The article proposes a conceptual framework for creating a new scenario for the utility sector, which will be used for efficiently increasing operation of tourism infrastructure objects. Using empirical research, two scenarios are suggested: an optimistic one, where smart technologies facilitate the traveler's life, and a pessimistic one, where technologies do not affect the course of the journey. Also, the linear regression method was used to create the forecast in accordance with the offered scenario. Presented scenarios help identify how smart technologies can make the traveler's life easier by providing fast and efficient travel planning through online applications, and also, show the negative consequences, when technologies do not work properly or unforeseen circumstances arise, leading to delays, disrupted plans, and inconveniences during the journey. The authors noted that the scientific novelty of this research lies in its consideration of the impact of smart technologies on decision-making processes in complex travel situations. A forecast of the number of tourists, and travelers to the studied countries until 2024, was made.